COMPARATIVE STUDY OF ATTITUDES OF GENERAL AND SPECIAL TEACHER TRAINEES TOWARDS INCLUSIVE EDUCATION - Panthri, Kamlesh Nandani (International Journal of Research -GRANTHAALAYAH, 2025)
Inclusive education is a transformative approach that aims to provide equitable learning opportunities to all students, including those with special needs, within mainstream classrooms. The successful implementation of inclusive practices largely depends on the attitudes and readiness of teachers. This study investigates and compares the attitudes of general and special teacher trainees towards inclusive education in Jaipur city. A total of 300 teacher trainees (150 general and 150 special) were randomly selected from various teacher training institutions in Jaipur. A descriptive survey method was employed, and data were collected using a self-administered attitude scale developed for this purpose. The data were analyzed using statistical tools such as mean, standard deviation, and independent samples t-test. Findings revealed that general teacher trainees exhibited significantly more positive attitudes toward inclusive education compared to special teacher trainees. The difference in mean attitude scores between the two groups was found to be statistically significant at the 0.05 level. The study concludes that while both groups recognize the importance of inclusive education, there is a need to strengthen special education training programs to promote more inclusive mindsets. The study offers suggestions for curriculum enhancement, increased practical exposure, and attitudinal development for both groups of trainees.